2018
DOI: 10.1016/j.gore.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Using gene expression in patients with endometrial intraepithelial neoplasia to assess the risk of cancer

Abstract: Patients diagnosed with an endometrial cancer precursor lesion on biopsy may be found to have endometrial cancer at the time of subsequent surgery. The current study seeks to identify patients with endometrial intraepithelial neoplasia (EIN) on biopsy that may be harboring an occult carcinoma. Immunohistochemical stains for gene loss of expression (LOE) for 6 genes, PTEN, ARID1A, MSH6, MSH2, MLH1, and PMS2, were performed on 113 biopsy specimens with EIN. For the 95 patients with follow-up histology, 40 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…At the end of the study selection process, seven studies were finally included in the systematic review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the study selection process, seven studies were finally included in the systematic review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…For the ‘flow and timing’ domain, two studies were considered at unclear risk of bias (loss of patients unexplained or unclear ) and 5 at low risk.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the scoping review were reported according to the Preferred Reporting Items for Systematic reviews and Meta-criteria and were included in our review. We included 24 primary studies, [9][10][11][13][14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] three meta-analyses, [17][18][19] and one poster presentation. 12 The characteristics of the 28 included studies are shown in Table 2.…”
Section: Stage 5: Summarizing Resultsmentioning
confidence: 99%
“…12 The characteristics of the 28 included studies are shown in Table 2. Five studies were multicentric, 17-19, 27,35 five studies were from Turkey, 11,15,20,23,25 four studies were from the USA, 12,13,21,22 two studies were from the UK, 14,16 two studies were from Canada 10,34 and there was one study from each of Australia, 9 South Korea, 24 France, 26 Belgium, 28 Italy, 29 Denmark, 30 Greece, 31 Norway, 32 Taiwan, 33 and China. 36 These studies included the data of 7409 patients and recorded 2377 concurrent EC cases (32.1%).…”
Section: Stage 5: Summarizing Resultsmentioning
confidence: 99%
See 1 more Smart Citation